POTENCIAL DE PREDAÇÃO DE CHRYSOPERLA EXTERNA (HAGEN, 1861) (NEUROPTERA:CHRYSOPIDAE) SOBRE TENUIPALPUS HEVEAE BAKER (ACARI: TENUIPALPIDAE) EM SERINGUEIRA - Sales, Ana Carolina; Maruyama, Wilson; Toscano, Luciana; Da Silva, Eliamara (ANAIS DO ENIC, 2018)
-